2022
DOI: 10.1021/acsami.1c17279
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Field Emission from Ultrananocrystalline Diamond-Decorated Carbon Nanowalls Prepared by a Self-Assembly Seeding Technique

Abstract: Vertically aligned nanographite structures, the so-called carbon nanowalls (CNWs), are decorated with ultrananocrystalline diamond particles by an electrostatic self-assembly seeding technique, followed by short-term growth in plasma chemical vapor deposition, to enhance field emission efficiency and stability. A nanodiamond suspension diluted with a dispersion medium with high wettability on CNWs enables seeding of diamond nanograins consisting of nanoparticles of 3–5 nm in diameter on CNWs with high uniformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…(see, e.g., Refs. [60][61][62][63][64][65][66]). The new knowledge we have gained expands the possibilities of CNW films applications, in particular, in photonics and optoelectronics.…”
Section: Discussionmentioning
confidence: 99%
“…(see, e.g., Refs. [60][61][62][63][64][65][66]). The new knowledge we have gained expands the possibilities of CNW films applications, in particular, in photonics and optoelectronics.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although the turn-on electric field is not significantly improved and is still much higher than those of many reported ultralow turn-on field emitters, these two treatment methods greatly extend the lifetime of CNT emitters, which is longer than the lifetime of those field emitters with lower turn-on electric fields. [16][17][18][19][20][21][22]24,44,45 Therefore, this simple and costsaving treatment gives CNT emitters an advantage over other types of CNT emitters as well as other carbon material-based emitters.…”
Section: Long-term Stability and Lifetime Testingmentioning
confidence: 99%
“…Hence, because of the low lifetime of CNT field emitters, researchers gradually turned to finding other carbon materials with better field emission properties, such as diamond or nano walls. [16][17][18][19][20] These carbon-based field emitters have been found to have lower turn-on voltages and more stable emission currents and longer lifetime, especially after certain chemical treatments. However, these types of emitters usually have a relatively more complex and costly fab-rication process.…”
Section: Introductionmentioning
confidence: 99%
“…3 Based on the idea of increasing electron emission sites, Teii et al fabricated diamond-decorated carbon nanowalls, which showed a lower E to , higher emission current density, and superior emission stability than that of pristine carbon nanowalls. 9 To tailor the bandgap of the emitter material, Chen et al doped P impurities into the lattice of SiC nanoparticles to constitute the localized impurity states in the vicinity of the conduction band edge, thereby decreasing the work function, and the corresponding b of the P-doped SiC nanoparticles could be as high as 5508, which was significantly higher than that of pure SiC nanoparticles (1283). 10 To date, SiC is recognized as a potential candidate for developing high-performance FE cathodes because of its outstanding physical characteristics, such as high-temperature stability, high thermal conductivity, exceptional mechanical behavior, and unmatched resistance to thermal shock, which are favorable for its functioning in extreme working conditions (e.g., high power, high temperature, and high voltage).…”
Section: Introductionmentioning
confidence: 99%
“…3 Based on the idea of increasing electron emission sites, Teii et al fabricated diamond-decorated carbon nanowalls, which showed a lower E to , higher emission current density, and superior emission stability than that of pristine carbon nanowalls. 9 To tailor the bandgap of the emitter material, Chen et al doped P impurities into the lattice of SiC nanoparticles to constitute the localized impurity states in the vicinity of the conduction band edge, thereby decreasing the work function, and the corresponding β of the P-doped SiC nanoparticles could be as high as 5508, which was significantly higher than that of pure SiC nanoparticles (1283). 10…”
Section: Introductionmentioning
confidence: 99%